2019
DOI: 10.1007/s00592-019-01286-w
|View full text |Cite
|
Sign up to set email alerts
|

Duodenal adipose tissue is associated with obesity in baboons (Papio sp): a novel site of ectopic fat deposition in non-human primates

Abstract: Aims: Ectopic fat is a recognized contributor to insulin resistance and metabolic dysfunction, while the role of fat deposition inside intestinal wall tissue remains understudied. We undertook this study to directly quantify and localize intramural fat deposition in duodenal tissue and determine its association with adiposity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…13 Our study provided evidence on QCT could serve as a reliable technique in quantifying PFD in patients with T2DM, and we found that high PFD positively correlated with the degree of insulin resistance and may play an important role in islet cell dysfunction in the late-stage T2DM. [14][15][16][17] It has been reported in the literature that long-term exposure to a high-fat diet leads to interlobular and intralobular fat accumulation, inflammatory cell infiltration, and pancreatic fibrosis in rat pancreas, thereby impairing normal pancreatic architecture, resulting in pancreatic fat fibrosis and impaired islet function. Due to the inability to distinguish the deposition of fat within acinar cells, β-cells, or pancreatic adipose tissue, various synonyms have been used for the accumulation of pancreatic fat, including pancreatic hyperlipidemia, pancreatic steatosis, pancreatic fat replacement, and pancreatic fat infiltration, fatty pancreas and NAFPD (non-alcoholic fatty pancreas).…”
Section: Discussionmentioning
confidence: 99%
“…13 Our study provided evidence on QCT could serve as a reliable technique in quantifying PFD in patients with T2DM, and we found that high PFD positively correlated with the degree of insulin resistance and may play an important role in islet cell dysfunction in the late-stage T2DM. [14][15][16][17] It has been reported in the literature that long-term exposure to a high-fat diet leads to interlobular and intralobular fat accumulation, inflammatory cell infiltration, and pancreatic fibrosis in rat pancreas, thereby impairing normal pancreatic architecture, resulting in pancreatic fat fibrosis and impaired islet function. Due to the inability to distinguish the deposition of fat within acinar cells, β-cells, or pancreatic adipose tissue, various synonyms have been used for the accumulation of pancreatic fat, including pancreatic hyperlipidemia, pancreatic steatosis, pancreatic fat replacement, and pancreatic fat infiltration, fatty pancreas and NAFPD (non-alcoholic fatty pancreas).…”
Section: Discussionmentioning
confidence: 99%